Effects of senescence on the expression of BDNF and TrkB receptor in the lateral geniculate nucleus of cats - TONG, Chuan-Wang (Dongwuxue Yanjiu, 2015)
To explore the neural mechanisms mediating aging-related visual function declines, we compared the expressions of brain-derived neurotrophic factor (BDNF) and its high affinity receptor-tyrosine kinase B (TrkB) between young and old adult cats. Nissl staining was used to display neurons in each layer of the lateral geniculate nucleus (LGN). The BDNF- and TrkB receptor-immunoreactive neurons were labeled immunohistochemically, observed under optical microscope and photographed. Their neuronal density and immunoreactive intensity were measured. Results showed that the mean density of the Nissl stained neurons in each LGN layer were comparable between old and young adult cats, and their BDNF and TrkB proteins were widely expressed in all LGN layers. However, compared with young adult cats, both the density and optical absorbance intensity of BDNF- and TrkB-immunoreactive cells in each LGN layer in old cats were significantly decreased. These findings indicate that the decreased expressions of BDNF and TrkB proteins in the LGN may be an important factor inducing the compromised inhibition in the central visual nucleus and the functional visual decline in senescent individuals.